2021
DOI: 10.1186/s13010-021-00099-6
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenology, Saudi Arabia, and an argument for the standardization of clinical ethics consultation

Abstract: Background The purpose of this study is to make a philosophical argument against the phenomenological critique of standardization in clinical ethics. We used the context of clinical ethics in Saudi Arabia to demonstrate the importance of credentialing clinical ethicists. Methods Philosophical methods of argumentation and conceptual analysis were used. Results We found the phenomenological critique of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The service in Illinois "has published on the aspects of their service that are amenable to quantification. Ethicists employed at the service have not come to regard what can be quantified as the only important parts of consultation practice" [6]. At first glance it seems that the ethicists are in fact in a position to avoid the proceduralist trap.…”
Section: Brummett and Muaygil's Misunderstandingsmentioning
confidence: 99%
See 4 more Smart Citations
“…The service in Illinois "has published on the aspects of their service that are amenable to quantification. Ethicists employed at the service have not come to regard what can be quantified as the only important parts of consultation practice" [6]. At first glance it seems that the ethicists are in fact in a position to avoid the proceduralist trap.…”
Section: Brummett and Muaygil's Misunderstandingsmentioning
confidence: 99%
“…Bishop never suggested that ethicists would stop caring about the qualitative aspects of CEC but that proceduralism would lead to them being unable to engage in practices that will emphasize those aspects, because procedures reliably de-emphasize the qualitative. Another of Brummet and Muaygil's examples is a service in California "where the procedural approach is markedly influential, " yet the "clinical ethicists are equally invested in enhancing the consultation experience, with all its messy human elements, for patients and practitioners alike" [6]. What at first seems to be a strong piece of evidence for their case is immediately undermined when they add that, "Through nonformal debriefing sessions, consultants attempt to better understand stakeholders' perceptions of the consultation process in order to better optimize CEC" [6].…”
Section: Brummett and Muaygil's Misunderstandingsmentioning
confidence: 99%
See 3 more Smart Citations